THE INFLUENCE OF LEADERSHIP AND WORK MOTIVATION ON ORGANIZATIONAL COMMITMENT AND EMPLOYEE PERFORMANCE AT PT TIRAN GROUP MAKASSAR - irayani; Muh Asdar; Nurjanah Hamid (Scientia Integritas Utama, 2023)
In order for businesses to thrive in the era of globalization, human resource issues are currently their top priority. Organizations are required to be able to offer appropriate feedback from the work done by an employee in terms of leadership and motivating workers. Employees, as executors of work, will always try their best to be able to carry out their obligations properly. With this research, organizational commitment and employee performance of PT Tiran Group Makassar are examined in relation to leadership and work motivation. This type of research is hypothesis testing with quantitative methods. The population is all employees of PT Tiran Makassar with a sample of 83 respondents. Data were analyzed by means of paths using SPSS 22. The findings show that leadership at PT Tiran Makassar has a positive and substantial impact on worker performance, while work motivation has a positive and significant impact on organizational commitment. At PT Tiran Makassar, organizational dedication has a good but negligible impact on staff performance. Employee performance at PT Tiran Makassar is positively and significantly influenced by work motivation, with organizational commitment as the intervening variable.